Field translators professional competence formation peculiarities - Bukhkalo, Svetlana Ivanovna; Ageicheva, Anna Oleksandrivna; Belyanskiy, Oleksandr Mykolaiyvych; Pshychkina, Nataliia Heorhiivna; Rozhenko, Inesa Vitaliivna (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article is devoted to the study of the formation of professional competences during the training of specialists in field translation, in particular, the regularities of English-Ukrainian translation. It is determined by the need for a comprehensive study of the linguistic, cultural, and psychological features of English-Ukrainian translation in the field. Such professional competences of field translation are gaining great importance today, as the expansion of socio-political, economic, and cultural ties between states is observed. Professional competence main aspects are investigated. A comprehensive analysis of professional competence formation while training field translation specialists is performed. Peculiarities of professional competence formation are revealed. Exploring main aspects of training field translation is described. It is determined that it is important for a translator to have professional competence. The results of this work are of great importance to field translation specialists. The importance of professional competence formation while training field translation specialists is analyzed.

Стаття присвячена дослідженню формування професійних компетенцій під час підготовки фахівців польового перекладу, зокрема, закономірностям англо-українського перекладу. Це зумовлено необхідністю комплексного дослідження мовних, культурних та психологічних особливостей англо-українського перекладу в галузі. Такі професійні компетенції галузевого перекладу сьогодні набувають великого значення, оскільки спостерігається розширення суспільно-політичних, економічних, культурних зв’язків між державами. Досліджено основні аспекти професійної компетентності. Здійснено комплексний аналіз формування професійної компетентності при підготовці спеціалістів з перекладу на виїзні теми. Виявлено особливості формування професійної компетентності. Описано вивчення основних аспектів навчально-польового перекладу. Визначено, що для перекладача важливо мати професійну компетентність. Результати цієї роботи мають велике значення для спеціалістів-перекладачів.
Особливості формування професійної компетентності перекладачів галузевого перекладу
Keywords: field translation; training; professional competence; professional competences formation; галузевий переклад; навчання; професійна компетентність; формування професійних компетентностей